DISTANCE TECHNOLOGIES IN THE PROCESS OF FORMING THE ENGLISH-LANGUAGE COMPETENCE OF FUTURE ENGINEERS - Halatsyn, Kateryna; Feshchuk, Alla (Scientific Journal of Polonia University, 2022)
The urgency of forming English-speaking competence through distance technologies is caused by modern requirements of training specialists in the technical sphere and epidemiological situation in the world. The article aims to define the essence of English-speaking competence formation through distance technologies. In order to realise the defined goal, it is essential to solve the following tasks: 1) to substantiate the essence of the process of formation of English-speaking competence with application of distance technologies; 2) to analyse the specificity of formation of English-speaking competence of future engineers in the course of the use of distance technologies at English lessons. Distance technologies of developing English-speaking competence of future engineers are considered as a set of forms and methods aimed at forming and improving the competence of reading, translation, listening of authentic audio texts, video texts, scientific articles; improving the competence of English-speaking written speech; systematisation of English-speaking grammar competence through tests with the help of distance platforms and Internet-resources. It was found that English-language professional competence integrates knowledge of professional terminological vocabulary, skills of working with English-language professional texts and documents, and background knowledge of socio-cultural features of the language under study. The author proposes goals for the use of distance learning technologies in the course “Academic English”.